Determination of β-Agonist Residues in Animal-Derived Food by a Liquid Chromatography-Tandem Mass Spectrometric Method Combined with Molecularly Imprinted Stir Bar Sorptive Extraction - Jiwang Tang; Jianxiu Wang; Shuyun Shi; Shengqiang Hu; Liejiang Yuan (Journal of Analytical Methods in Chemistry)
A novel clenbuterol molecularly imprinted polymer (MIP)-coated stir bar was prepared and applied to the determination of six β-agonists in animal-derived food. Characterization and various parameters affecting adsorption and desorption behaviours were investigated. The extraction capacities of clenbuterol, salbutamol, ractopamine, mabuterol, brombuterol, and terbutaline for MIP coating were 3.8, 2.9, 3.1, 3.5, 3.2, and 3.3 times higher, respectively, than those of the NIP coating, respectively. The method of MIP-coated SBSE coupled with HPLC-MS/MS was developed. The recoveries in pork and liver samples were 75.8–97.9% with RSD from 2.6 to 5.3%. Limits of detection (LODs) and limits of quantification (LOQs) were 0.05–0.15 μg/kg and 0.10–0.30 μg/kg, respectively. Good linearities were obtained for six β-agonists with correlation coefficients (R2) higher than 0.994. These results indicated the superiority of the proposed method in the analysis of β-agonists in a complex matrix.